Combining ability and heterosis analysis for grain yield and it,s components in bread wheat(Triticum aestivum L.) - سناء بلال شيخ; بولص خوري; مجد درويش (Latakia University Journal -Biological Sciences Series, 2023)
This study was carried out in AL- SHEER -LATTAKIA and Tishreen University, during 2020/2021 and 2021/2022 seasons. Five bread wheat (Triticum aestivum L.) genotypes were used L-1300,L-1302,L-68017, L-66233 , L-68467. Half diallel mating method was followed to get 10 hybrids . The hybrids and their parents were sown in the second season, using a randomized complete block design with three replication to estimate general combining ability GCA, specific combining ability SCA, genetic components, and both mid and better parent heterosis for traits; spike height ,number of grains per plant, thousand kernel weight, and grain yield per plant .The results indicated additive gene action in all trait inheritance, except thousand kernel weight which was controlled by non-additive genes. Three parents had high general combiners effects for grain yield, (L-68467) , ( L-1300), (L-68017) .the derived progenies of these parents in the breeding program will have high gene inheritance . Many hybrids with desirable specific combining ability effects were obtained from parents with desirable general combining ability effects, which also have both mid and high parents heterosis, including (L-1300* L-68467) ,( L-68017* L-68467). thus hybrids coud be used for selection in segregating generations in order to reach high yielding wheat lines. Key words :Bread wheat, Combining ability ,genetic components, Heterosis .